Physiological Respons of Bali and Simbal Cattles on the Thermal Environtment of Lowland and Highland Areas in Lombok Island - Lalu Wira Pribadi; Rr. Agustien Suhardiani; Tahyah Hidjaz; M. Ashari; Happy Poerwoto; Rina Andriati (Jurnal Biologi Tropis, 2021)
The effort to increase productivity of Bali cattle in Lombok Island made use of crossbreeding with exotic breeds, such as Simmental, Limousine, Charolais, Hereford, and Brahman breed, in which Simmental was suggested the best one. However, replacing indigenous with exotic breed might in fact create significant problem, especially low tolerance on harsh environment condition and increased work to feed each animal because of higher growth and greater size at maturity. This study that mean objective to investigate the physiological respons of Bali and Simbal cattleÃÂ  on the thermal environment of lowland and highland areas in Lombok island, was carried out by measure the rectal temperature (BT, oC), respiration rate (RR, resp/min), and heat tolerance coefficient (HTC) of 320 cattles in lowland and 280 cattle in highland, each consisted of pure Bali breed (B), crossbred of B x Simmental (SB), backcross of SB x Simmental (SBS), and backcross of SB x Bali (SBB). Each genotype consist of male and female, and 24-36 months of age. All cattle observed are ordered to be similar condition with BCS 3-5. The thermal condition of lowland and highland are measured from air temperature (oC), relative humidity (%), and temperature humidity index (THI). Data were analysed by using Anova and further test using HSD-test. Results of the study shows, the daily temperature and THI data obtained for the lowland environment are in considered to thermal stress zone for beef cattle, whereas those of found for the highland are within range of safety zone for cattle production. Physiological response shuch as BT, RR, and HTC, were significantly higher for cattle in the lowland than those in highland. The crossbreds cattle with higher proportion of Simmental genetic showed higher BT, RR, and HTC in the lowland, but became decrease in highland environment by higher decreasing index. It could be conclused that environmental condition in lowland with average THI of 80.02 lead to coused thermal stress to genotypes of Simbal cattle based on HTC wich in average of 2.91; however in highland wich average THI of 69.39 each genotype of cattle shows physiological responses in the normal range.ÃÂ